Implementasi Metode Pembelajaran Mind Mapping Untuk Meningkatkan Hasil Belajar Peserta Didik Dalam Pembelajaran Sejarah di Kelas XI IPS 3 SMAN 9 Semarang Tahun Ajaran 2022/2023 - Dian Amalia Kusumaningtyas (Historia Pedagogia, 2025)
This research aims to improve student learning outcomes by enhancing the learning process in the subject of Indonesian Life during the Japanese Occupation and to determine the extent of the increase in student activity and learning outcomes through the mind mapping learning method. This research was conducted at SMAN 9 Semarang, with the subjects being 36 students of class XI IPS 3. This research is a type of classroom action research, and the learning method used is mind mapping. The research was conducted in two cycles. The steps of this research began with a pretest to determine the initial abilities of the students, followed by the provision of the taught material. Then, students in groups created a mind map (a creative and effective way of note-taking that can be combined with colors, symbols, lines, and images that match the way the brain works) about the lesson material presented by the teacher and then presented it in front of the class. The next stage was a posttest to determine the understanding and learning success achieved by the students. From the research results, it can be concluded that the learning process in the subject of Indonesian Life during the Japanese Occupation using the mind mapping method showed an improvement in student learning outcomes. This is evident from the increase in the average posttest scores: the average score in cycle I was 74 with a learning mastery of 75%; and in cycle II, the average score was 80 with a learning mastery of 86%. This increase met the determined Minimum Competency Criteria (KKM) and learning mastery. The conclusion of this research is that student learning outcomes can be improved through the mind mapping learning method.